Case report: Treatment of two cases of recurrent/refractory early T-cell precursor acute lymphoblastic leukemia with venetoclax combined with the CAG regimen - Jiang, Yuxia; Ji, Lin; Jin, Xin; Wu, Haiying; He, Mingxia; Shen, Fenglin; Xu, Xiaofeng; Jiang, Huifang (Frontiers in Medicine, 2024)
Early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is a highly aggressive subtype of T-ALL. No standard chemotherapy regimen exists for patients with recurrent/refractory (R/R) ETP-ALL; in these patients, the primary goal of salvage therapy is to achieve remission as a foundation for consolidation and intensification treatments. This study reports cases of two patients with R/R ETP-ALL who underwent salvage therapy of venetoclax combined with the CAG regimen and achieved complete remission in the bone marrow. Flow cytometry results were negative for minimal residual disease. Both patients were bridged to allogeneic hematopoietic stem cell transplantation (HSCT) and in complete remission over a 3-year follow-up period. These cases show that the use of venetoclax combined with the CAG regimen may offer patients with R/R ETP-ALL an opportunity for allogeneic HSCT.